Has First‐Grade Core Reading Program Text Complexity Changed Across Six Decades?. Issue 1 (10th September 2015) - Fitzgerald, Jill; Elmore, Jeff; Relyea, Jackie Eunjung; Hiebert, Elfrieda H.; Stenner, A. Jackson
Abstract: The purpose of the study was to address possible text complexity shifts across the past six decades for a continually best‐selling first‐grade core reading program. The anthologies of one publisher's seven first‐grade core reading programs were examined using computer‐based analytics, dating from 1962 to 2013. Variables were Overall Text Complexity Level and nine text‐characteristic operationalizations: number of Syllables in words and Decoding (word structure); Age of Acquisition, Abstractness, and Word Rareness (word meaning); and Intersentential Complexity, Text Density, Phrase Diversity, and Noncompressibility (discourse level). Multilevel modeling was conducted. There were three main conclusions: (1) Overall Text Complexity levels trended toward more complexity in more recent years. (2) For four of the nine text characteristics, program years were different in the text characteristic progression from the beginning to the end of the first‐grade year. Initially in the fall, programs of later years exposed children to word structures (Syllables and Decoding) that were as easy or easier than in earlier years, but there was intense, and incomparable, control over gradually increasing the complexity of word structures throughout the year, ending the first‐grade year with the most complex word structures of any year. Simultaneously, as compared with earlier years, there was a pronounced diminished emphasis in the later program years on selected aspects of repetition and redundancy (Text Density and Phrase Diversity) across the first‐grade year. (3) Two of the six text characteristics, Age of Acquisition and Word Rareness, trended toward more complexity on average in the later program years.